Non-Temporal Components of Residential Real Estate Appreciation - Goetzmann, William N.; Spiegel, Matthew (The Review of Economics and Statistics, 1995)
This paper separates the components of capital appreciation returns in an asset market into fixed and stochastic portions. It proposes a control for the problem of fixed components in the capital appreciation return used in transactions-based return estimates. We find a consistent bias in the index resulting from repeat sales regressions which may be eliminated through simple methods. The sign and magnitude of the bias, as well as its systematic variation across property, suggest that it is caused by incremental home improvements, as well as by price risk. We propose a maximum likelihood method for estimating the first and second moments of the fixed and temporal components of real estate returns that relies upon relatively small samples. Copyright 1995 by MIT Press.